CLINICAL CASE: THE HYPNOSIS ANAESTHESIA - ADJUVANT ELEMENT IN THE CLASSICAL LOCAL ANAESTHESIA USED IN DENTISTRY - Geogiana Petrescu; Gheorghe Rotariu; Andrei Iliescu (Romanian Society of Oral Rehabilitation, 2016)
Any dentistry intervention needs an efficient anaesthesia for the toothache. Haw to offer treatment to a patient with difficult history in the way to obtain anaesthesia? The solution was to use classical local anaesthesia, potentate by the help of medical hypnosis techniques. Anaesthesia was obtained in a very good time in dentistry - 12 minutes. In conclusion when the classical anaesthesia doesn't work, a psychological support can solve the problem. It is necessary to elaborate studies according to the local anatomy, the grade of anxiety and acceptability of the patient for the alternatives methods to obtain the anaesthesia.